2018
DOI: 10.1536/ihj.17-072
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Determinants of Obstructive Hypertrophic Cardiomyopathy Obtained Using Echocardiography

Abstract: SummaryThe morphological determinants of left ventricular outflow tract (LVOT) obstruction in hypertrophic cardiomyopathy (HCM) are not completely understood. We aimed to identify the anatomical risks of the obstruction using echocardiography.Fifty patients with untreated HCM were classified into two groups: those with LVOT pressure gradient (LVOTPG) !30 mmHg (obstructive HCM [HOCM] group) and those with LVOTPG < 30 mmHg (HNCM group). The echocardiographic morphological variables were analyzed to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The result is a drop in pressure, known as the Venturi effect [ 31 ], which causes the AML to be pulled anteriorly into the LVOT. Given the ability of SAM to predict obstruction in HCM as demonstrated by Nara et al [ 18 ], this may explain why our results indicate AML anatomy metrics are highly predictive of LVOTO, despite relatively poor identification performance.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The result is a drop in pressure, known as the Venturi effect [ 31 ], which causes the AML to be pulled anteriorly into the LVOT. Given the ability of SAM to predict obstruction in HCM as demonstrated by Nara et al [ 18 ], this may explain why our results indicate AML anatomy metrics are highly predictive of LVOTO, despite relatively poor identification performance.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, studies using three-dimensional transoesophageal echocardiography and multidetector computed tomography have suggested that the LVOT is elliptical in shape, not round [ 33 ]. Therefore, the 2D LAX view may result in the underestimation of the LVOT diameter as it does not always portray the longest span of the outflow tract, thus this may have introduced a systematic error in these measurements [ 18 ].…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…LVOT obstruction is a hallmark of more severe symptoms and worse prognosis in patients with HCM 16,17 . Previous studies indicated that circulating biomarkers representing myocardial injury (cardiac troponin I, cTnI), cardiac function (N‐terminal pro‐brain natriuretic peptide, NT‐pro BNP), and inflammation (high sensitivity C‐reactive protein, hs‐CRP) played important roles in predicting adverse outcomes in HCM patients 18‐20 .…”
Section: Introductionmentioning
confidence: 99%